Key underwater habitat types of the northern Baltic Sea : An assessment of biodiversity and ecosystem functions - Kaikkonen, Laura; Jernberg, Susanna; Haavisto, Fiia; Boström, Christoffer; Gustafsson, Camilla; Kiviluoto, Suvi; Kostamo, Kirsi; Kuningas, Sanna; Kuosa, Harri; Lakso, Essi; Långnabba, Annica; Nygård, Henrik; et al. (Springer Nature, 2026)
Effective management of marine ecosystems requires understanding linkages between biodiversity and ecosystem functioning. While key species have been identified in many marine systems, the functions provided by different habitats have not been comprehensively synthesised in the region, limiting the ability to identify key habitats. Here, we assess the current state of knowledge on biodiversity and ecosystem functions associated with benthic and pelagic habitat types in the northern Baltic Sea. Drawing on literature, data and expert assessments, we evaluated 49 habitat types, identifying 750 habitat type-function linkages. Of these, 35% were supported by Baltic Sea literature and 29% by expert opinion, while one-third remained unassessed due to data gaps. Our findings highlight key habitat types with high functional importance and reveal major knowledge gaps and research biases across habitats. This synthesis provides a science-based foundation for marine spatial planning, ecosystem service assessment, and sustainable management of northern Baltic Sea biodiversity.
Keywords: Baltic sea; benthic habitats; biodiversity; ecosystem functions; expert knowledge; pelagic habitats